Cost-effectiveness of a photopethysmographic procedure for screening for atrial fibrillation in 6 European countries - Steffen Wahler; Ralf Birkemeyer; Dimitrios Alexopoulos; Zbigniew Siudak; Alfred Müller; Johann-Matthias von der Schulenburg (Health Economics Review, 2022)
Background: Strokes cause an estimated annual health care burden of 170 billion euros across Europe. Atrial fibrillation is one of the major risk factors for stroke and increases the individual risk 4.2-fold. But prevention with anticoagulants may reduce this risk by 70%. Screening methods are employed to detect previously undetected atrial fibrillation. Screening studies in various European countries show a high degree of undetected atrial fibrillation. This study aims to assess the cost-effectiveness of systematic screening with a smartphone application, named Preventicus Heartbeats. It is a hands-on screening tool for use on smartphone to diagnose AF with high sensitivity and specificity. Methods: A previously published model for calculating screening cost-effectiveness was extended to 6 European countries covering a wide range in terms of treatment costs and epidemiologic parameters. Results: The use of screening lowers the cost per case in countries with comparatively high levels of health care costs (Switzerland: - exteuro75; UK: - exteuro7). Moderate higher costs per case were observed in 4 countries (Greece: exteuro6; Netherlands: exteuro15). Low levels of health care costs result in less or no potential for further cost reduction (Poland: exteuro20; Serbia: exteuro33). In all countries considered, the model showed an increase in effectiveness measures both in the number of strokes avoided and the quality adjusted life years. The number of strokes avoided per 1000 participants ranged from 2.52 (Switzerland) to 4.44 (Poland). Quality-adjusted life-years per case gained from screening ranged from 0.0105 (Switzerland) to 0.0187 (Poland). The screening procedure dominated in two countries (Switzerland, UK). For the remaining countries, the incremental cost effectiveness ratio ranged from exteuro489/QALY (Greece) to exteuro2548/QALY (Serbia). Conclusion: The model results showed a strong dependence of the results on the country-specific costs for stroke treatment. The use of the investigated screening method is close to cost-neutral or cost-reducing in the Western European countries and Greece. In countries with low price levels, higher cost increases due to AF screening are to be expected. Lower costs of anticoagulation, which are expected due to the upcoming patent expiry of direct anticoagulants, have a positive effect on the cost result.
Keywords: 330; Atrial fibrillation; Screening; Prevention of stroke; Cost-effectiveness analysis